2018
DOI: 10.24917/20845456.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Dydaktyka geografii – teoria i metodologia (na przykładzie Bułgarii)

Abstract: Understanding, mastering and applying new ideas in geography didactics is the most proper way to achieve a high professionalism in geography education in Bulgaria. Such professionalism implies three prerequisites: a scientifically based (and not only intuitive) professional activity, high and sustainable results and a clear positive attitude towards it. The high professionalism is the required basis for successful solving the current problems of Bulgarian geography education which are of different nature: trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The main achievement and advantage for the author is to adapt these activities in the curriculum for the regional development. Other authors think that Life and practice undoubtedly have demonstrated the need for permanent improvement of teachers' training and further mastering (including geography ones), without which it is impossible to achieve the expected [9]Aspects for adaptation can be presented in the fields like:…”
Section: Training Firm Conception and Its Implementation In Regional Developmentmentioning
confidence: 99%
“…The main achievement and advantage for the author is to adapt these activities in the curriculum for the regional development. Other authors think that Life and practice undoubtedly have demonstrated the need for permanent improvement of teachers' training and further mastering (including geography ones), without which it is impossible to achieve the expected [9]Aspects for adaptation can be presented in the fields like:…”
Section: Training Firm Conception and Its Implementation In Regional Developmentmentioning
confidence: 99%